THE COMPARATIVE OF VILLAGE INCOME BEFORE AND DURING THE COVID-19 PANDEMIC IN REGENCIES/CITIES ON SUMATERA ISLAND. - Rahma Wati; Yuliana Sari; Yevi Dwitayanti (UNHI Press, 2023)
The intention of this research is to compare the financial situation of villages before and during the covid-19 epidemic by looking at their initial revenue, village funds, village funds allocations, financial help, and other income. Sixty samples were collected before the Covid-19 epidemic and another sixty were collected during it, making them representative of a mixed sample of the community. For this study, data from 2018-2021 was sampled on purpose according to predetermined criteria. Data was analyzed using a Paired Sample T-Test. Village Original revenue and Financial Assistance were consistent before and after the Covid-19 epidemic, although revenue from village funds, village fund allocations, and other sources varied significantly.